Features of Nigerian English in the Spoken and Written English of Undergraduates at Nigerian Universities - Nwokoji, Chukwuemeka (NIU Journal of Social Sciences, 2024)
This study examined the features of Nigerian English in the spoken and written English of undergraduates in Nigeria Universities. The objectives of this study are to identify the features of Nigerian English that characterize the spoken and written language of students in the university and to investigate the sociolinguistic factors that influence the use of Nigerian English features among the students. The theoretical framework of this study is based on Labov’s Sociolinguistic theory which focuses on the idea that the way a language is spoken and written differs across individuals as well as across situations encountered by the same individual. Using the descriptive research design and the questionnaire as research instrument, data was collected from a sample of 400 students using the purposive sampling method to determine the sample size. Findings revealed that English as a dynamic and evolving variety is shaped by sociolinguistic factors which manifest in the language of university students. Also, the Nigerian English features are more prevalent in the spoken English than the written form. The researcher recommended that Nigerian universities should consider implementing language awareness program as to help students recognize and understand the linguistic features of Nigerian English as part of the linguistic heritage of the country.